Sports ethics for sport management professional - Thornton, Patrick K.; Champion, Walter T.; Ruddell, Larry (Jones & Bartlett, 2012)
Sports management professionals are confronted with many ethical decisions during their career. It is essential that they are equipped to make the right decision when faced with a difficult situation. Sports Ethics for Sports Management Professionals provides students with the necessary tools to make ethical decisions in the sports management field. It presents several ethical models that the sports management professional can use as a platform to make ethical decisions